2022
DOI: 10.1155/2022/4126217
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis on the Key Influence of Adolescent Health Information Literacy Using Big Data Analysis Technology under Social Network Environment

Abstract: Purpose/Significance. This paper aims to explore the influence mechanism of adolescent health information literacy on health behavior. Method/Process. 13–19 year olds are taken as the survey objects to investigate their health information literacy through a questionnaire. Health information literacy mainly includes health information needs, acquisition, evaluation, use, and behaviors. A total of 252 adolescents’ data were collected in this study, and model testing was performed with the help of regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%